Implementasi Algoritma Clustering untuk Efisiensi Energi di Wireless Sensor Network - Dona Wahyudi; M. Udin Harun Al Rasyid; Iwan Syarif (Jurnal Inovtek Polbeng Seri Informatika, 2019)
Energy efficiency is a major challenge in implementing WSN, and the use of routing and clustering protocols are several ways that can maximize energy use. Energy efficiency is needed because WSN has limited energy resources from the battery and its placement in an area that is not always monitored making battery replacement difficult or cannot be done. This study uses AOMDV (Ad hoc On-demand Multipath Distance Vector) to provide a delivery path from source to destination. In addition, the arrangement of a balanced number of cluster members is done for each cluster. From the results of the experiment, it was found that by regulating the number of balanced cluster members has better energy efficiency results.